Risk factors and early prediction of clinical deterioration and mortality in adult COVID‐19 inpatients: an Australian tertiary hospital experience. Issue 4 (13th April 2022) - Brook, Rowena; Lim, Hui Yin; Ho, Prahlad; Choy, Kay Weng
Abstract: Background: Early recognition of severe COVID‐19 is essential for timely patient triage. Aims: To report clinical and laboratory findings and patient outcomes at a tertiary hospital in Melbourne, Australia. Methods: This is a retrospective study of adult inpatients with COVID‐19 admitted to Northern Health from March to September 2020. Data were extracted from electronic medical records. Results: Key admission data were available for 182 patients (median age 67.0 years (interquartile range, 47.9–83.1); 51.1% female). Fifty‐six (30.8%) were from residential care. One hundred and seventeen (64.3%) patients were assigned Goals of Patient Care (GOPC) A or B and 65 (35.7%) GOPC C or D. Comorbidities were present in 135 patients (74.2%). 63.2% of patients received antibiotics, 6.6% had antivirals, 45.6% received systemic glucocorticoid and 3.3% had tocilizumab. Fifty‐six (30.8%) developed clinical deterioration (24 requiring ventilation, 21 receiving critical care, 34 died). Overall, inhospital clinical deterioration was significantly associated with older age ( P < 0.001), history of diabetes ( P = 0.038), lower lymphocyte count ( P = 0.002) and platelet count ( P = 0.004), higher neutrophil‐to‐lymphocyte ratio ( P = 0.002), elevated fibrinogen ( P = 0.004), higher serum ferritin ( P = 0.027) and C‐reactive protein (CRP; P = 0.002). The accuracy of the 4C Deterioration model was moderate, with an area under the curve (AUC) of 0.79 (95% confidence interval (CI), 0.68–0.90) compared with an AUC of 0.77 (95% CI, 0.76–0.78) in the original validation cohort. Conclusions: In the present study, high neutrophil‐to‐lymphocyte ratio, abnormal d ‐dimer, high serum CRP and ferritin appear to be useful prognostic markers.